Fresh off the boat. The complete first season [videorecording (DVD)] - Park, Randall; Yang, Hudson, 2003-; Wu, Constance, 1982-; Huang, Eddie, 1982- (20th Century Fox Home Entertainment, 2015)
"Join TV's funniest new family and flashback to the '90s! Twelve-year-old hip-hop enthusiast Eddie Huang and his family make their way from D.C.'s Chinatown to Orlando where his dad, Louis, tries to make his new steakhouse a success. His mom, Jessica aims to understand the culture clash and dominate suburbia. While his brothers fit right in, Eddie's still tries to get a seat at the table--any table--in the school cafeteria"--Container.